Rare case of nephrocalcinosis in the distal tubules caused by hereditary renal hypouricaemia 3 months after kidney transplantation. (July 2016) - Okabayashi, Yusuke; Yamamoto, Izumi; Komatsuzaki, Yo; Niikura, Takahito; Yamakawa, Takafumi; Katsumata, Haruki; Kawabe, Mayuko; Katsuma, Ai; Nakada, Yasuyuki; Kobayashi, Akimitsu; Koike, Yusuke; Miki, Jun; et al.
Abstract: We report a rare case of nephrocalcinosis caused by hereditary renal hypouricaemia 3 months after kidney transplantation. A 41‐year‐old man who underwent living‐related kidney transplantation from his father was admitted to our hospital for a protocol biopsy; he had a serum creatinine (S‐Cr) of 1.37 mg/dL and no proteinuria. Histologically, there was no evidence of rejection or calcineurin inhibitor toxicity, although scattered nephrocalcinosis was observed in the distal tubules. Perioperatively, the patient had a serum uric acid (S‐UA) of 1.9 mg/dL with a fractional excretion of uric acid (FEUA) of 29% (normal, <10%) and UA clearance of 26.8 mL/min (normal, 7.3–14.7 mL/min) 3 days after kidney transplantation. The donor also had a relatively low S‐UA of 2.4 mg/dL and high FEUA of 10.3%. Subsequent DNA direct sequencing followed by restriction fragment length polymorphism revealed that both the recipient's and donor's urate transporter 1 ( URAT1 ) gene had a heterozygous nonsense mutation in exon 5 (C889T). Further, the immunoreactivity of antibodies for the C terminus of URAT1 revealed a partial deletion. De Galantha and von Kossa staining revealed that the nephrocalcinosis was due to urate crystals and calcium stones. Therefore, we diagnosed hereditary renal hypouricaemia. We directed the patient to avoid hard exercise, drink plenty of water, and alkalize the urine. The 1‐year follow‐up allograft biopsy showed no evidence of nephrocalcinosis in the distal tubules. This is the first report of nephrocalcinosis in the distal tubules as a diagnostic clue to hereditary renal hypouricaemia. We also review the related literature.